“I Have a Job, But . . .”: A Review of Underemployment - McKee-Ryan, Frances M.; Harvey, Jaron (Journal of Management, 2011)
This article reviews the underemployment literature, providing a comprehensive integrative overview of underemployment research. Underemployment, which occurs when a worker is employed in a job that is inferior by some standard, is linked to a broad range of negative outcomes for employees. This article builds on Feldman’s 1996 model of underemployment and identifies relevant theoretical perspectives and dimensions of underemployment, as well as reviewing the empirical research on the relationships between underemployment’s antecedents and outcomes. Suggestions for future research are offered, with particular attention on career implications, the effects of underemployment on an employee’s identity, and the importance of “choice” for underemployed employees. Finally, recommendations for improving the methodological rigor of underemployment research are provided.